(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Snehakalpana plays an important role in treatment both internally and externally. When used for topical application it has the potential to diffuse locally in soft tissues and produce the desired therapeutic action. The specific pharmaceutical blend of these contents can result in a more effective formulation. Malatyadi Taila is one such formulation mentioned in Chakradutta, clamied to be beneficial in Darunaka. The ingredients are Malati patra, Karaveera moola, Chitraka moola, Karanja beeja. Therefore, this formulation is selected to study its efficacy in Darunaka. The main pharmaceutical procedures involved in the preparation of Malatyadi Taila are Shodhana, Churna nirmana, Kalka nirmana and Taila paka. The specific pharmaceutical blend of these contents can result in a more effective formulation. Therefore, the present study has been planned to standardize the method of preparation of Malatyadi Taila according to the method explained in the classical literature.